Epicardial Fat: Physiological, Pathological, and Therapeutic Implications - Juan Salazar; Eliana Luzardo; José Carlos Mejías; Joselyn Rojas; Antonio Ferreira; José Ramón Rivas-Ríos; Valmore Bermúdez (Cardiology Research and Practice)
Epicardial fat is closely related to blood supply vessels, both anatomically and functionally, which is why any change in this adipose tissue’s behavior is considered a potential risk factor for cardiovascular disease development. When proinflammatory adipokines are released from the epicardial fat, this can lead to a decrease in insulin sensitivity, low adiponectin production, and an increased proliferation of vascular smooth muscle cells. These adipokines move from one compartment to another by either transcellular passing or diffusion, thus having the ability to regulate cardiac muscle activity, a phenomenon called vasocrine regulation. The participation of these adipokines generates a state of persistent vasoconstriction, increased stiffness, and weakening of the coronary wall, consequently contributing to the formation of atherosclerotic plaques. Therefore, epicardial adipose tissue thickening should be considered a risk factor in the development of cardiovascular disease, a potential therapeutic target for cardiovascular pathology and a molecular point of contact for “endocrine-cardiology.”